The usage of feedback as a strategy for developing speaking skill - Gaguancela Juca, Karen Anai (2025)
The limitations derived from the usage of traditional methods in teaching English have been considered a key factor that affects the development of oral skill, which is why the usage of active strategies such as feedback has been proposed. In this research, the effectiveness of feedback was analyzed as a strategy applied to strengthen oral skills in sixth grade students of the “Dr. Leonidas García Ortíz” School of Basic Education. For this, three instruments were used: an observation guide, a feedback record and a semi-structured interview, through which the initial level of performance was identified, the strategy was applied and its effects were evaluated. Notable improvements in aspects such as pronunciation, fluency, vocabulary, interaction and sentence construction were evident after the intervention. These improvements were associated with the systematic use of different types of feedback, which made it possible to correct errors, increase participation and reinforce confidence when speaking. Despite the progress, certain difficulties persisted, which is why it was considered necessary to maintain teaching support in later stages. In conclusion, the feedback strategy was considered effective in promoting the development of oral skill in English.